A study on comparisons of customer preferencen’s towards islamic and conventional personal loan / Noormariana Mohd Din - Mohd Din, Noormariana (2011)
This paper reports study on the customer preferences towards the Islamic and conventional personal loan. The objective of the study is to determine the comparisons of customer preferences towards for both banking sector in the personal loan product. For this study, the primary data are used and the researcher had distributed the questionnaire among 95 employees at UMK from the different department. The data collected was tested by using reliability, descriptive and cross tabulation testing. The finding also illustrates which preferences will be acts as the factor to choose the Islamic and conventional banking. This indicates that most of the respondents having the different preferences towards Islamic and conventional personal loan. It is important to investigate this because it will help the banking sector for make some of improvement in terms of service quality, structure of financing, charge rate, types of loan and protection in provide the personal loan